Slouching toward New Humanism - Contini, Paolo; Osmanaj, Elisabeta (Frontiers in Sociology, 2023)
In the contemporary era, novel social and cultural patterns have emerged, prompting the social sciences to engage in timely reflections on current phenomena and the very essence of humanity. These models have undergone significant transformations, so much so that New Humanism appears to be a viable prospect. It is upon this premise that all the observations put forth in this study are centered, operating under the assumption that the evolution of knowledge is a continuous process, marked by perpetual paths of research and reflection. It is well established that Humanism represents a recurring theme in our daily lives, with its premises inscribed on the walls of cities and subways. In the modern era, the concept of Humanism is liberated from its “classical” meanings. As such, it becomes crucial to consider New Humanism as a supplement for the soul, capable of invigorating spirituality, restoring energy, and instilling ethics rooted in solidarity, recognition, and mutual respect among individuals. This mission serves as a formidable catalyst, motivating and mobilizing the consciences and intelligence of individuals, particularly those in the Western world. Furthermore, this pressing need necessitates the adoption of conceptualization and analytical reconstruction pathways, which are functional in actualizing the perspective of New Humanism, establishing it as a proposition of contemporary culture. It is often implicit in widespread individualism, which tends to manifest exaggerated and exasperating tones of hyper-individualism. It is thus essential not to overlook the doctrine espoused by classical Humanism, which suggests that it is possible to be disenchanted and yet remain builders of utopias, and realists who can see new lands and infinite ideal worlds. Indeed, human beings can transcend existing barriers, using tradition as a viaticum for the future, as evidenced by numerous disciplinary fields.